The teaching of public relations in Brazil in relation to the digital technologies - Rhoden, Valmor; Rhoden, Juliana Lima Moreira (Organicom, 2014)
Currently, in 2014, public relations completes one hundred years in Brazil, of which 47 in the area of teaching. This article discusses the teaching of the area in our land in relation to the digital technologies. One discusses the importance of rethinking the curricula in a way that can cope with the new reality faced by graduates concerning the digital technologies, using the current demands and expectations of the working world. We begin by assuming that the teaching is not preparing adequately the student of the area for the digital scenario. The inclusion of digital skills in Brazilian courses is a true challenge, inasmuch as it is still an isolated and incipient process. Meanwhile, in the working world the graduates of the area must learn how to manage digital communication.